ANALISA PENGARUH KETEBALAN LEMPENGAN BESI (Fe) TERHADAP INDUKSI MAGNETIK YANG DITIMBULKAN OLEH BEBERAPA MEREK TELEPON SELULER - Ikrah Noprianti; Erwin '; Salomo ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
Nowadays, a cellular telephone is predicted to generate the effect of electromagnetic radiation on the users. In this research, the measurement of magnetic induction generated by three cellular telephones (sample A, B and C) was demostrated. The measurement was performed in two directions namely horizontal and vertical directions. In order to measure the magnetic induction, was used a Pasco magnetic probe 2162. The magnetic induction in the horizontal direction was measured with the distance of 0,5 cm from the cellular telephone. The effect of a slab of iron with various thicknesses namely 1-4 mm on magnetic induction was also studied. The results of this research showed that the value of magnetic induction generated by the cellular telephone sample A is the highest among brand B and C with the value of 7.73300x10-4 Tesla and followed by sample B and C with the value of 3.6241x10-4 Tesla and 1.41615x10-4 Tesla respectively. The value of magnetic induction in vertical direction decreases very significantly with the distance. Moreover, the magnetic induction increases when a slab of iron with the thickness of 1 mm to 4 mm was introduced.